Can remission be in juvenile idiopathic arthritis without the use of biological agents? - S. I. Valieva; A. A. Glazyrina; N. N. Kuleshov; M. S. Dzis; S. Kh. Kurbanova; A. S. Sologub; E. A. Korobiyants; V. T. Yusupova (Современная ревматология, 2019)
Objective: to evaluate the efficiency and safety of therapy with subcutaneous (SC) methotrexate (MTX) in patients with juvenile idiopathic arthritis (JIA) without systemic manifestations.Patients and methods. The paper presents the results of a prospective study of the efficacy and safety of MTX in 247patients aged 1 to 17 years with articular variants of JIA, as well as the frequency of indications for prescribing biological agents for this category of patients. JIA occurred without systemic manifestations in all the patients, including 106 with oligoarticular articular JIA, 94 with rheumatoid factor (RF)-negative polyarticular JIA, 15 with RF-positive polyarticular JIA, 20 with enthesitis-related JIA, and 12 with psoriatic arthritis. JIA was diagnosed according to the ILAR criteria. After verification of the diagnosis, all the patients were prescribed SC injections of MTX at a dose of 15 mg/m2/week.Results and discussion. After 3 months of MTX therapy, 50 and 70% improvements according to the ACR pediatric criteria were registered in 65 and 53% of the patients, respectively. After 6, 9, and 12 months of therapy, the stage of inactive disease or remission was observed in 44.5, 85, and 100% of the patients, respectively.Conclusion. Parenteral MTX administration contributes to the achievement of disease remission and the restoration of joint functions in patients with JIA without extra-articular manifestations. Along with its high therapeutic efficacy, MTX had a good tolerability and a favorable safety profile.